Influence of the heat treatment temperature on the MAO coating produced in the Ti–25Ta–25Zr alloy - Kuroda, Pedro Akira Bazaglia (2023)
The main objective is to carry out several heat treatments to change the phases and some characteristics of the MAO coatings formed in Ti–25Ta–25Zr alloy in order to understand how the oxides or morphology of the MAO coating influence hardness, elastic modulus, adhesion, and wear resistance. The results showed that the MAO coating is amorphous and constituted by TiO2, ZrO2, Ta2O5, and CaCO3, and the heat treatments promoted the formation of Ti2O3 and CaO and the degradation of Mg at 800 °C. Increasing the temperature of the heat treatments reduced the pore size and, consequently, decreased roughness (minimum value of 0.77 μm in the condition of 500 °C), increased hardness (maximum of 673 HV), and improved wear resistance (3 × 10−15 m/N−1). When heat treatments are carried out above 600 °C, cracks are observed throughout the coating. Under these conditions, the roughness is altered and is no longer influenced only by pores size. Cracks increase the roughness of the coatings, reaching a maximum value of 1.16 μm. Therefore, there is a decrease in the coatings’ hardness, and the alloy becomes more sensitive to abrasive wear phenomena. At 800 °C, the hardness is 494 HV, and the wear rate ∼40 × 10−15 m2/N Regarding elastic modulus, the Ti–25Ta–25Zr alloy with the MAO coating subjected to heat treatment at 400 °C has a lower elastic modulus. Coatings subjected to high temperatures (above 500 °C) have an HF1 rating indicating high adhesion.